2018
DOI: 10.1096/fj.201700027r
|View full text |Cite
|
Sign up to set email alerts
|

The trafficking protein, EHD2, positively regulates cardiac sarcolemmal K ATP channel surface expression: role in cardioprotection

Abstract: ATP-sensitive K (K) channels uniquely link cellular energy metabolism to membrane excitability and are expressed in diverse cell types that range from the endocrine pancreas to neurons and smooth, skeletal, and cardiac muscle. A decrease in the surface expression of K channels has been linked to various disorders, including dysregulated insulin secretion, abnormal blood pressure, and impaired resistance to cardiac injury. In contrast, up-regulation of K channel surface expression may be protective, for example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Caveolae have also been reported in the heart to function as sarcolemma ‘reservoirs’ to buffer membrane tension (Sinha et al 2011). A critical link between EHD2 and caveolae stability has also recently been demonstrated by Coetzee and colleagues showing EHD2 is necessary for stabilising caveolae, and for co-localisation of a sub-population of K ATP channels leading to a proposed cardioprotective role of EHD2 against ischaemic damage (Yang et al 2018). Other reports have characterised EHD2 in COS-7 cells as a transcriptional supressor, regulating gene expression via a nuclear localisation signal (NLS), a conserved nuclear export signal (NES) and SUMOylation site within the helical linker between the N-terminal and C-terminal domains (Pekar et al 2012).…”
Section: Role Of Sarcolemma ‘Repair’ Proteins In the Heartmentioning
confidence: 71%
“…Caveolae have also been reported in the heart to function as sarcolemma ‘reservoirs’ to buffer membrane tension (Sinha et al 2011). A critical link between EHD2 and caveolae stability has also recently been demonstrated by Coetzee and colleagues showing EHD2 is necessary for stabilising caveolae, and for co-localisation of a sub-population of K ATP channels leading to a proposed cardioprotective role of EHD2 against ischaemic damage (Yang et al 2018). Other reports have characterised EHD2 in COS-7 cells as a transcriptional supressor, regulating gene expression via a nuclear localisation signal (NLS), a conserved nuclear export signal (NES) and SUMOylation site within the helical linker between the N-terminal and C-terminal domains (Pekar et al 2012).…”
Section: Role Of Sarcolemma ‘Repair’ Proteins In the Heartmentioning
confidence: 71%
“…Immunocytochemistry. As previously described (24), isolated rat cardiomyocytes were plated on glass coverslips and fixed with 4% paraformaldehyde. Cells were permeabilized with 0.1% Triton X-100 and blocked with 5% donkey serum in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether the increased mean patch K ATP channel current is due to enhanced membrane targeting, we biochemically assessed the surface expression of K ATP channels. As in our previous study (24), we performed surface biotinylation of Kir6.2 with an extracellular Avi tag (Avi-Kir6.2), which functions and traffics similar to wildtype Kir6.2. The Avi-Kir6.2/SUR1 channels were expressed in HEK-293 cells and we confirmed that they are palmitoylated similarly to the wild-type channel (SI Appendix, Fig.…”
Section: Palmitoylation Does Not Increase the K Atp Channel Surfacementioning
confidence: 99%
“…The significance of EHDs in this process however remains unclear. In addition, EHD paralogs, more specifically EHD3, appear to be crucial for the structural and functional specialization of membrane tubules of cardiomyocytes, a process attributed to endocytic recycling of critical proteins required for normal excitability of cardiac myocyotes 54–58 …”
Section: Physiological Functions Of Ehdsmentioning
confidence: 99%